Prevalence of robotic surgery in Pakistan - Naveed, Hufsa; Tooba Naveed; Areeba Farooqui (Journal of the Pakistan Medical Association, 2023)
Dear Editor, Robot-assisted surgery is a medical procedure that utilizes specific innovation that improves the abilities of one’s surgical skills. It enables surgeons to perform complicated surgeries in difficult-to-reach areas via small incisions. The innovation comprises of 1-Surgical arms with tiny instruments with wrists at the tip, 2-Special camera that gives improved, amplified 3D perspectives on the region 3-Surgical Control Centre where the surgeon controls the instrument and the camera. (1) Experts who utilize robotic surgery find that it develops exactness, versatility, and control during the movement and permits them to see complex areas that are not visible through other techniques. Utilizing robotic surgery procedures, experts can do delicate and complex medical procedures that may be inconvenient with traditional procedures (2) Often, robotic surgery procedures make beyond belief prominent clinical therapies possible. The benefits of fewer obtrusive medical procedures include fewer bothers, less blood loss; speedier recovery; and fewer unmistakable scars. (2) Automated robotic surgery is now practice in Pakistan by the Sindh Institute of Urology and Transplantation. Around the globe, robotic surgery has caught the attention of many physicians and is also used for other organ surgeryDespite mainstream thinking, it doesn't imply that robots are doing your medical procedure. All things being equal, a specialist controls robotic arms with outrageous accuracy. During robotic surgery, a specialist utilizes a PC to control the robotic arms that go through the method. Robotic surgery gives her unparalleled adaptability and accuracy during medical procedures. (3) In conclusion, Pakistan needs to care for an enormous pool of patients connected with the prostate, kidney, gall bladder, different tissues and organs. The current ratio of 0.473 physicians per 1,000 population in Pakistan is inadequate to maintain the nation's health. (4) Healthcare system frameworks all over the world have been changed over the most recent couple of years, bringing about a more prominent need and interest for surgical schooling outside operation theatres Lastly, the general well-being area of Pakistan ought to likewise make plans to import equipment,/ machines from organizations with the goal that it is made accessible in hospital across the country. Subsequently, this will help our careful division in its progression from a medical procedure to robotic assisted priesion medical procedure.